The effects of plasma treatment on UV-curable epoxyacrylate coatings - (:unkn) unknown (Fiber Society, 2014)
In this study, difunctional epoxyacrylate UV-light sensitive oligomers have been synthesized at various carboxyl/epoxide ratios and characterized by Fourier transform infrared spectroscopy (FTIR), acid value, epoxy equivalent weight (EEW) measurements. These oligomers were coated onto the plasma treated and untreated polyester cord fabrics and then cured by UV light. The effects of carboxyl/epoxide ratio and plasma treatment have been investigated by using scanning electron microscopy (SEM) and optical microscopy images.
Keywords: Adhesive; Epoxyacrylate; Polyester cord fabric; UV-curing